The Effect of Mindfulness Practice on the Learning Process of Learners - Gunawan, Riyan; Burmansah, Burmansah; Seneru, Wistina; Tang, Troi Bao (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
The aim is to determine the effect of mindfulness practices on learners' learning process. Frequently encountered problems, such as stress, academic anxiety, distraction, and lack of motivation, which can hinder learners' concentration and academic performance. This study used a quantitative approach with a survey method involving 102 learners as respondents. The research instrument is a questionnaire with a Likert scale that measures learners' awareness on four mindfulness indicators, namely the body, feelings, thoughts, and objects of thought. The results showed that the practice of mindfulness had a positive effect on learners' learning process, with the majority of respondents being in the high category on body awareness, feeling awareness, and mind awareness. However, awareness of mental objects was in the medium category. Overall, mindfulness practices have a significant influence on learners' learning process and the rest is influenced by other factors.